Protective Effect of Allyl Isothiocyanate in an Experimentally Induced Rat Model for Dry Eye Syndrome - Muz, Omer Ersin; Orhan, Cemal; Tuzcu, Mehmet; Er, Besir; Morde, Abhijeet Ashok; Padigaru, Muralidhara; Şahin, Kazım (Taylor & Francis Inc, 2022)
Purpose Growing evidence emphasizes the role of inflammation and oxidative stress in the pathogenesis of Dry Eye Syndrome (DES). Concordantly, the importance of agents targeting the inflammatory cascade and oxidative stress in the treatment is also progressively increasing. Herein, the study has investigated the protective effects and underlying mechanism of allyl isothiocyanate (AITC) on the ocular surface in a benzalkonium chloride (BAC)-induced dry eye rat model. Methods A total of twenty-one Wistar albino rats were used to form the following three groups: Control, BAC, BAC + AITC. DES was established by topical application of BAC (four times daily for two weeks) in two groups, of which one group was treated with AITC (10 mg/kg BW daily oral dosage) for four weeks. Rats were monitored by dry eye diagnostic tests during the study period, and eventually, corneal tissues were used to evaluate for histopathologic analyzes and inflammatory and oxidative status. Results A significant improvement was observed in various histopathologic and ophthalmologic findings, including tear volume, tear film integrity, ocular surface damage, ocular inflammatory signs, corneal thickness, and edema through AITC supplementation. AITC prominently balanced the inflammatory status and oxidative stress by lowering key proinflammatory mediators (NF-kappa B, TNF-alpha, IL-1 beta, IL-6, and IL-8) and increasing the activities of antioxidant enzymes (SOD, GSH-Px). Also, levels of protective tear proteins, including Muc1, Muc4, and Muc5 were recovered with AITC supplementation. Conclusion AITC alleviates clinical and histopathologic signs related to DES. Antioxidative and anti-inflammatory properties of AITC play a significant role in the mechanism of action.
Keywords: allyl isothiocyanate; dry eye syndrome; oxidative stress; inflammation; ocular surface